Quality of Life in Married Women: Religiosity and Psychological Immune System as Predictors - Raudatussalamah Raudatussalamah; Reni Susanti; Hasbullah Hasbullah; Mukhlis Mukhlis; Elyusra Ulfah; Salmiyati Salmiyati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
Women are known to be particularly susceptible to mental health issues, which can have a detrimental impact on various aspects of their lives, including physical, psychological, and social well-being. To enhance their quality of life, it is crucial to identify protective factors such as religiosity and psychological immune. Therefore, this research explored the relationship between religiosity, psychological immune system, and married women’s quality of life. The research employed a quantitative correlational approach, with data collected from 207 married women aged 22-63 years who identified as Muslims using the convenience sampling method. Based on SEM Partial Least Square analysis, it was concluded that religiosity indirectly affects quality of life through psychological immune system with a t value of 4.722 (p = .000) and a total effect t value of 2.803 (p = .003). Increasing religiosity is important in improving psychological immune system to improve quality of life.